Discriminative Dissolution Method Using the Open-Loop Configuration of the USP IV Apparatus to Compare Dissolution Profiles of Metoprolol Tartrate Immediate-Release Tablets: Use of Kinetic Parameters - Bruno Solis-Cruz; Daniel Hernandez-Patlan; Elvia A. Morales Hipólito; Guillermo Tellez-Isaias; Alejandro Alcántara Pineda; Raquel López-Arellano (MDPI AG, 2023)
The use of the USP IV apparatus (flow-through cell) has gained acceptance in recent years due to its versatility and ability to discriminate due to its hydrodynamic conditions. Therefore, the objective of the present study was to develop a discriminative dissolution method in the USP IV apparatus using the open-loop configuration, as well as to propose a method to compare non-cumulative dissolution profiles obtained in the open-loop configuration considering kinetic parameters and validate its predictive power through its comparison with independent and dependent methods using five commercial immediate-release tablet drugs (one reference drug and four generic drugs) of metoprolol tartrate as a model drug. The comparison of the non-accumulated dissolution profiles consisted of determining the geometric ratio of Cmax, AUC0∞, AUC0Cmax, and Tmax (kinetic parameters) of the generic/reference drugs, whereby generic drugs "C" and "D" presented the highest probability of similarity since their 90% confidence intervals were included, or they were very close to the acceptance interval (80.00-125.00%). These results were consistent with the f2, bootstrap f2, and dissolution efficiency approaches (independent models). In conclusion, the proposed comparison method can be an important tool to establish similarity in dissolution profiles and to facilitate the development/selection of new formulations and positively ensure bioequivalence in clinical studies.